The Factors Which Lead Students’ Dropout from Public Secondary Schools in Al’Ain City, Exploring It - Alkaabi, Khamis Fatima Abdulla; Noor, Mohd Asri Bin Mohd (European Journal of Social Science Education and Research, 2023)
For any instructive organization, understudies are generally significant. Colleges and schools have no an incentive without students. The instructive cycle is an incorporated interaction including the family, the school and the whole local area to arrive at viable yields. There are a number of factors that negatively affect at-risk students’ retention in school and graduate such as socioeconomic status. Phenomenon of dropout where thousands of students dropped out is prevalent and constant in urban schools across the United States (Brown, 2015). This research is important for academic reason; it gives academic practitioners vital information that can be utilized to develop the education. The information was collected by interviews questions with students. The information collected were analyzed by using coding, theme and sub-nodes with Nvivo program. The research showed that the factors affect in Retention of secondary stage’s students in Al Ain.